The Effect of CLT Method On Students’ Speaking Skillat The Second Grade of MTSN 1 Kolaka - Zakaria Zakaria; Rani Royani (JETL (Journal of Education, Teaching and Learning), 2017)
This research presented about the effect of CLT Method on Students’ Speaking Skill at the Second Grade of MTsN 1 Kolaka. The research question was “is there significant effect of CLT Method on Students’ Speaking Skill at the Second Grade of MTsN 1 Kolaka?” The objective was to find out the effect of CLT method, the data and information about students’ speaking skill at the second grade of MTsN 1 Kolaka. The design of this research was quasy expriment in two classes with pre-test and post-test design. The sample were class VIII MTsN 1 Kolaka of 208 students and took 54 students as the sample. The instruments were speaking test comprehension. Data collection techniques in this research were giving pre-test, treatment, and post-test. The result it was found that in expriment class the mean score of pre-test (52,2) was smaller than the mean score of post-test (62,6) it means that the increased of the students’ speaking SKILL was 37% (0,51) and the value of was bigger than at the significant level 0,05 and degree of freedom –26, it means that   was rejected and  was accepted. It can concluded that there was an effect of CLT  method on students’ speaking skill at the second grade of MTsN 1 Kolaka.